2011
DOI: 10.1370/afm.1197
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preventive Messages Tailored to Family History on Health Behaviors: The Family Healthware Impact Trial

Abstract: PURPOSE We wanted to determine the impact of automated family history assessment and tailored messages for coronary heart disease, stroke, diabetes, colorectal, breast, and ovarian cancer on preventive behaviors compared with a standard preventive message. METHODSThe study was a cluster-randomized clinical trial that included 41 primary care practices, the majority in the Midwest, using Family Healthware, a self-administered, Web-based tool that assesses familial risk for the diseases and provides personalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
115
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 26 publications
1
115
2
Order By: Relevance
“…Findings from the Family Healthware Impact trial indicate modest increases in physical activity levels after a targeted intervention. 33 Results from our cancer screening analysis showed that women with an FMH of breast or ovarian cancer were nearly 1.7 times more likely to be up to date with mammography screening as compared with women without an FMH of cancer, but nearly 15% were not up to date with recommendations for women at average risk for breast cancer. Although men and women with an FMH of CRC were 2.8 times more likely to be recently screened as compared with men and women without an FMH of cancer, nearly 29% were not currently up to date with recommendations for average-risk individuals.…”
Section: Discussionmentioning
confidence: 78%
“…Findings from the Family Healthware Impact trial indicate modest increases in physical activity levels after a targeted intervention. 33 Results from our cancer screening analysis showed that women with an FMH of breast or ovarian cancer were nearly 1.7 times more likely to be up to date with mammography screening as compared with women without an FMH of cancer, but nearly 15% were not up to date with recommendations for women at average risk for breast cancer. Although men and women with an FMH of CRC were 2.8 times more likely to be recently screened as compared with men and women without an FMH of cancer, nearly 29% were not currently up to date with recommendations for average-risk individuals.…”
Section: Discussionmentioning
confidence: 78%
“…Only a few of these instruments are being examined prospectively for accuracy [66][67][68] or utility. 60 The My Family Health Portrait tool, developed through the US Centers for Disease Control and Prevention, performed as well as a detailed history obtained by a genetic counselor for four common diseases and less well for two others. 69 Some tools are being assessed by their ability to engage and educate consumers and healthcare providers.…”
mentioning
confidence: 99%
“…A recent report of the Family Healthware project suggests that healthy subjects made aware of family risks selfreport more physical activity and better nutrition, at least in the short term and without validation. 60 Much more robust investigations need to be performed, including examining clinical outcomes as measured by mortality, morbidity, or quality of life. Even if clinical utility were shown by some measure, how 72 will those at increased risk be subject to unfair discrimination in the workplace, in various types of insurance, or in other aspects of life?…”
mentioning
confidence: 99%
“…7 A study of this tool in primary care practices found that messages that were tailored to an individual's familial risk were associated with some lifestyle changes. 21 Use of the Genetic Risk Assessment on the Internet with Decision Support, a web-based tool that was not EHR-integrated, was associated with a significant increase in appropriate referrals to genetic clinics and with an improvement in practitioners' confidence in managing familial cancer. 22 The Genetic Risk Early Assessment Tool (GREAT) used IVR to collect family history before a cancer genetics visit, but was not EHR integrated.…”
Section: Discussionmentioning
confidence: 99%